118 Use of Spinal Cord Diffusion Tensor Imaging to Quantify Neural Ablation and Evaluate Outcome After Percutaneous Cordotomy for Intractable Cancer Pain. (1st August 2016) - Vedantam, Aditya; Hou, Ping; Chi, Linda; Dougherty, Patrick M.; Viswanathan, Ashwin
Abstract: INTRODUCTION: Percutaneous cordotomy for intractable cancer pain has variable efficacy. One potential cause is the inability to quantify neural ablation. Diffusion tensor imaging (DTI) can quantify microstructural changes within the spinal cord after neural injury. We aimed to determine if DTI metrics within the spinal cord could quantify neural ablation and evaluate early postoperative outcomes. METHODS: This prospective study was performed on patients undergoing percutaneous CT-guided cordotomy for unilateral intractable cancer pain. Pre- and postoperative quantitative sensory testing as well as visual analog scale (VAS) pain assessments were performed. Postoperative DTI images of the high cervical spinal cord were obtained on postoperative day 1. Fractional anisotropy (FA) and mean diffusivity (MD) were measured from regions of interest drawn within the spinal cord at the level of the lesion. DTI metrics were correlated with the number of lesions as well as early postoperative pain outcomes. RESULTS: Seven consecutive patients (4 male, 3 female, mean age 53.8 ± 4.6 years) were studied. FA of the hemicord on the side of the lesion was significantly lower than on the contralateral side (0.54 vs 0.63, P < .001). FA was significantly lower in patients with more than 2 lesions (n = 4) compared with those with 2 lesions (n = 3) (0.52 vs 0.56, P = .04). MD correlated with change in pain detection threshold in the region of maximum pain on postoperative day 1 ( r = −0.93, P = .008, n = 6). MD of the lesion also correlated with the improvement in VAS score at 1 week ( r = 0.88, P = .008). CONCLUSION: DTI of the spinal cord was sensitive to the number of lesions as well as early improvement in pain scores after cordotomy. DTI of the cervical spinal cord is a potential biomarker of neural ablation after percutaneous cordotomy for intractable cancer pain, and may have a role in evaluating patients with a poor outcome after cordotomy.